Primary treatment of anaerobic landfill leachate using activated carbon and limestone - Batch and column studies - Foul, A.A.; Aziz, H.A.; Isa, M.H.; Hung, Y.-T. (2009)
Leachate generated from an old landfill in Taiping, Perak, Malaysia contains high colour, COD, iron and ammoniacal nitrogen. Activated carbon–limestone mixture was used as a primary treatment process. More than 86% of colour and COD, 95% of iron, and 48% of ammoniacal nitrogen were removed by a mixture of activated carbon and limestone (15:25 by volume) in the batch study compared with 70, 80 and 90% respectively, by column study on the first five days. Both Langmuir and Freundlich isotherms had fitted well with the experimental data. The adsorption kinetics followed the pseudo-second-order model indicating that chemisorption or ion exchange was the rate-controlling step in the adsorption.